Local Peace Agreements and the Return of IDPs with Perceived ISIL Affiliation in Iraq - Parry, Jacqueline (World Bank, Washington, DC, 2022)
Between 2015 and 2020, communities across Iraq signed local peace agreements (LPAs) aimed at setting the foundations for peaceful relations between internally displaced persons (IDPs) accused of siding with ISIL and their ‘home’ communities. This paper maps the characteristics of eight such LPAs and compares each with the scholarly expectations regarding what makes a ‘good’ peace agreement. It also considers how the characteristics of each LPA affected conditions for safe and sustainable IDP return. Overall, the study found that a failure to include IDPs directly in LPA negotiations did not appear to compromise safe return but did potentially undermine sustainability—but at the same time, indirect representation of IDPs (through tribal leadership) enabled negotiations to occur that would otherwise be impossible; that the inclusion of women, youth and civil society contributed to the sustainability of IDP return but did not appear to influence safe return; that LPAs were an effective tool for addressing community concerns around the return of IDPs but typically prioritized community concerns over IDP rights, potentially creating new grievances; and finally, that mechanisms to implement and monitor each LPA were important for building community acceptance but empowered new actors and were vulnerable to co-optation.